Concurrent learning: How firms develop multiple dynamic capabilities in parallel - Bingham, Christopher B.; Heimeriks, Koen H.; Schijven, Mario; Gates, Stephen (Strategic Management Journal, 2015)
Much is known about the importance of dynamic capabilities. Yet, surprisingly little is known about how multiple dynamic capabilities might be developed in parallel, since most existing work explores a particular dynamic capability in isolation. Using rich quantitative and qualitative data on D ow C hemical's acquisitions, joint ventures, and divestitures over the past 20 years, we seek to address this gap. Besides contributing by adding fresh insights about managing growth and the utility of distributed practice, and by shedding light on positive and negative experience transfer, our core contribution is an emergent theoretical framework that develops the concept of “concurrent learning. ” Copyright © 2014 John Wiley & Sons, Ltd.